2022
DOI: 10.1021/acs.jafc.2c05753
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Inhibition Potential of AHL Acylase PF2571 against Food Spoilage by Remodeling Its Substrate Scope via a Computationally Driven Protein Design

Abstract: The N-acyl homoserine lactone (AHL) acylases are widely used as quorum sensing (QS) blockers to inhibit bacterial food spoilage. However, their substrate specificity for long-chain substrates weakens their efficiency. In this study, a computerassisted design of AHL acylase PF2571 was performed to modify its substrate scope. The results showed that the variant PF2571 H194Y, L221R could effectively quench N-hexanoyl-L-homoserine lactone and N-octanoyl-L-homoserine lactone without impairing its activity against l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Additionally, molecular dynamics simulation could be utilized to assist in mutant enzyme designing, evaluating the action mechanisms of the variant. For example, Wang, Cui et al (2022) used molecular dynamics simulation to test the action mechanisms of the variant of N-acylhomoserine lactone acylase. It was concluded that the substitution of residues 194 and 172 resulted in steric hindrance, which was more favorable for catalysis.…”
Section: Mechanism Exploration Of Enzyme Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, molecular dynamics simulation could be utilized to assist in mutant enzyme designing, evaluating the action mechanisms of the variant. For example, Wang, Cui et al (2022) used molecular dynamics simulation to test the action mechanisms of the variant of N-acylhomoserine lactone acylase. It was concluded that the substitution of residues 194 and 172 resulted in steric hindrance, which was more favorable for catalysis.…”
Section: Mechanism Exploration Of Enzyme Activitymentioning
confidence: 99%
“…For example, Wang, Cui et al. (2022) used molecular dynamics simulation to test the action mechanisms of the variant of N ‐acyl‐homoserine lactone acylase. It was concluded that the substitution of residues 194 and 172 resulted in steric hindrance, which was more favorable for catalysis.…”
Section: Applications Of Molecular Simulation To Food Protein–ligand ...mentioning
confidence: 99%
“…); secreting extracellular enzymes to degrade food nutrients; and forming mucus and biofilms on the surface of food. Studies have shown that when the number of bacterial colonies in food reaches 6lg CFU/mL, the main signal molecule in the QS system of Gram-negative bacteria, N-acylhomoserine lactone (AHL), can be detected [88]. Gram et al added the E. carolovora, which produces AHL and can hydrolyze pectin, to bean sprouts, and the storage test showed that it could accelerate the decay of bean sprouts [89].…”
Section: Solid Food Preservationmentioning
confidence: 99%
“…15,31 Finally, AHL acylases were recently shown to inhibit the spoilage of food caused by bacteria, which represents yet another application area for QQ technologies. 18,32 Given the above facts, the increased application potential of QQ enzymes is evident in various areas. However, it is worth noting the obstacles that limit their applicability.…”
Section: Introductionmentioning
confidence: 99%
“…However, while these enzymes show high potential for preventing food spoilage, the lack of optimized and cost-effective production is currently considered a major application obstacle. 18,22 Instead of devising processes for improving the applicability of individual AHL-degrading enzymes, we propose to focus on engineering this activity for already well-established Escherichia coli penicillin G acylase (ecPGA), best known for its role in the synthesis of semi-synthetic β-lactam antibiotics. [23][24][25][26] ecPGA represents a perfect template for engineering due to the availability of multiple high-quality crystal structures, broad knowledge of its properties, and multiple protocols for expression and purification, as documented by successful rational engineering cases.…”
Section: Introductionmentioning
confidence: 99%